2020
DOI: 10.11621/pir.2020.0406
|View full text |Cite
|
Sign up to set email alerts
|

!e Psychological Impact of Six Weeks of Lockdown as a Consequence of COVID-19 and the Importance of Social Support: A Cross-Cultural Study Comparing Spanish and Russian Populations

Abstract: Background. !e COVID-19 pandemic has been an unprecedented social and health emergency worldwide. Cross-cultural research on mental health during this situation is needed to better understand its consequences. Objective. To evaluate the di"erent psychological impacts of the crisis and lockdown situation during the #rst six weeks of COVID emergency measures in samples of the Spanish and Russian populations. Design. A cross-sectional study was conducted through an online survey (NSpain = 1041; NRussia = 743). !e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Individuals from the Hispanic culture highly value family, social connections, and support systems. Collectivist cultures such as the Hispanic culture maintain problems related to acknowledging mental-health issues within the family system (Ausín et al, 2020). Therefore, when confronted with mental-health distress, Hispanics are more likely to seek advice from families, peers, or religious leaders than psychiatric professionals (Ausín et al, 2020; Rogers et al, 2018).…”
Section: Hispanic Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals from the Hispanic culture highly value family, social connections, and support systems. Collectivist cultures such as the Hispanic culture maintain problems related to acknowledging mental-health issues within the family system (Ausín et al, 2020). Therefore, when confronted with mental-health distress, Hispanics are more likely to seek advice from families, peers, or religious leaders than psychiatric professionals (Ausín et al, 2020; Rogers et al, 2018).…”
Section: Hispanic Populationsmentioning
confidence: 99%
“…Social Support and Collaboration. Hispanic culture is influenced by collectivism; therefore, nurses and MHCs should include social-support groups, particularly family members, in the treatment plan of Hispanic clients (Ausín et al, 2020). Studies indicate that social support is a strong predictor of resilience among Hispanic individuals who have experienced trauma (Ausín et al, 2020; Saltzman et al, 2020), and a sense of social belonging helps Hispanic families cope with trauma in more positive ways (Abreu et al, 2020).…”
Section: Hispanic Populationsmentioning
confidence: 99%
“…5), повторивший большой пик продаж в первую волну. Понятно, что делать водку индикатором стресса не вполне корректно, но пока что замеры стресса в России во время эпидемии единичны [28], но широко представлены в западной Теория общесТвенного здоровья научной литературе [29], даже в сравнительном аспекте (например, [30]) или с обозначением источников стресса (например, финансовый стресс [31]).…”
Section: теория общественного здоровьяunclassified
“…Results from a Dutch population-based longitudinal study [23] showed that while emotional loneliness increased during the pandemic, social and social emotional loneliness did not show any significant changes. There have also been studies claiming that loneliness rates due to lockdowns caused by COVID-19 were high or higher (often conducted during or right after the first lockdown), for example [24][25][26][27][28], but data were not compared with prepandemic rates. A rapid review, reported by Pai and Vella [14], outlined the inconsistencies in the existing studies: differences in samples in terms of demographic characteristics, and discrepancies in the results.…”
Section: Introductionmentioning
confidence: 99%